Near-Infrared Magneto-Refractive Effect for Antiferro-Magnetically Exchange Coupled Co/Ru Multilayer Film in Transmission Configuration - Saito, S; Sato, H; Ooki, K; Akahane, K; Uchida, H (Journal of the Magnetics Society of Japan, 2019)
A magneto-refractive effect in a near-infrared (IR) region was investigated with a transmission configuration (T-MRE) for antiferro-magnetically coupled Co/Ru multilayer films. Applying dielectric function analysis based on an expanded Drude model that takes spin-dependent scattering into account, it was found that (1) a [Co(4 nm)/ Ru(0.7 nm)]10 multilayer film took parallel to antiparallel magnetization states at H = 14 kOe to 0 Oe, respectively, and (2) that T-MRE curves against H took the maximum in the near-IR region and the minimum in the middle wavelength IR region. (3) The magnitude and wavelength dependence of T-MRE were well fitted by using the expanded Drude model with ωp = 1.5 × 1016, τSAL = 0.66, and βSAL = 0.125, where τSAL and βSAL were self-averaged relaxation time and spin asymmetry, and ωp was the plasma angular frequency of conduction electrons. (4) According to calculation based on the expanded Drude model, the T-MRE of ΔT/T showed the maximum of 0.3% at around 700 nm, and in the longer wavelength region, it showed a saturated feature with a value of -1.3% at around 3 μm.